Tumor-penetrating peptide boosts bispecific T-cell engager antitumor efficacy for the pancreatic cancer - Zou, Lu; Chen, Jingjing; Bai, Xinyuan; Wang, Yingxin; Lu, Changchang; Wang, Qiaoli; Tuerhong, Subiyinuer; Li, Mengzhu; Zheng, Qinghua; Meng, Fanyan; Du, Juan (Frontiers in Immunology, 2025)
BackgroundOne of the main hurdles in solid tumors to the limited response of immunotherapy is the lack of sufficient T-cell infiltrate. This study aims to construct an iRGD-modified BiTE-directed T-cell therapeutic approach to enhance the treatment efficacy against KRAS G12V-mutated pancreatic cancer.MethodsWe used a novel bispecific T-cell engager (BiTE) targeting the HLA-A2/KRAS G12V complex and CD3 (HLA-A2/KRAS G12V-CD3 BiTE). By modifying with iRGD, we induced BiTE-mediated inward flow of activated effector T cells, specifically targeting the KRAS G12V mutation and improving tumor tissue penetration to address the problem of limited efficacy due to insufficient effector cells infiltration.ResultsThe results demonstrated that iRGD modification could promote tumor-specific lymphocyte infiltration and accumulation in tumor tissue, significantly inhibit tumor growth, and prolong survival in a xenograft pancreatic tumor model. This dual-action approach enhances T-cell infiltration by promoting transvascular and stromal penetration, greatly enhancing the efficacy of bispecific antibodies in solid tumors, leading to effective tumor eradication.ConclusionsThese findings strongly suggest further clinical validation of this iRGD-modified BiTE-directed T-cell therapeutic approach, potentially offering a more effective treatment option for patients with pancreatic cancer and other solid tumors.